Application of the RADEC learning model assisted with flipbook media to improve student's reading comprehension ability - Sulastyana, Erma; Anam, Rifat; Sunata, Sunata (Panicgogy International Journal, 2023)
This study aimed to improve student's reading comprehension skills through the role of the RADEC (Read-Answer-Discuss-Explain-Create) learning model assisted by flipbook media. One of the reasons for the low reading ability of students was the learning process at school. Therefore, the teacher had to be able to determine the appropriate learning model. This research was a Classroom Action Research (PTK) model of Kurt Lewin. It was carried out in two cycles, starting with pre-cycle, cycle 1, and cycle 2. The research subjects were 22 (twenty-two) grade 3 students at SDN 036 Ujungberung Bandung City. Data collection was carried out using a written test in the form of multiple-choice questions of 10 questions. The results showed that there was an increase in the percentage of completeness of learning outcomes. The pre-cycle showed 45% of students were complete and 55% incomplete, cycle I had 68% complete and 32% incomplete, and cycle II had 100% completed and 0% incomplete. Based on the results of the study, it could be concluded that the RADEC learning model assisted by flipbook media could improve the reading comprehension skills of grade 3 students. The results of this study indicated that, in general, the RADEC learning model improved student learning activities. Students were more active when the learning process took place with various syntaxes. In addition, the RADEC learning model supported students' reading comprehension skills during the implementation process. With the syntax Read, students' reading comprehension skills were trained and their information or insights were broadened before receiving the subject matter. The RADEC learning model was suitable for students in Indonesia whose reading literacy level was low compared to other countries. With the habit of doing reading activities before the learning process, students' interest in reading could be increased.